Lost in the green transition? Measurement and stylized facts - Causa, Orsetta (OECD Economics Department Working Papers, 2024)
Greening the economy entails jobs contracting in "high-polluting" economic activities and expanding in environment-friendly activities. Minimizing the corresponding transition costs is crucial to accelerate decarbonisation and reduce displacement costs for affected workers. Using individual-level labour force data for a large sample of European countries, this paper finds that the shares of green and high-polluting jobs remained approximately stable between 2009 and 2019, hinting at a slow or yet-to-come green transition in labour markets. Green and high-polluting jobs are unequally distributed across socioeconomic groups: women are under-represented in both green and high-polluting jobs, while green jobs are associated with higher educational attainment, and high-polluting jobs with lower educational attainment. Equally important from a policy perspective, the results show that high-polluting jobs are concentrated in rural areas. These results are confirmed by analyzing labour market transitions: for instance, while women are more likely to transition from study to job, they are significantly less likely to get a green job. Overall, the results suggest that well designed and targeted policies are needed to support efficient and inclusive labour market transitions in the greening economy: to minimize scarring effects for displaced workers, help individuals' upskilling and reskilling, and support the matching between workers and jobs in higher demand